Implementasi Kolaborasi Pemerintah Kota Cimahi dan Kantor Imigrasi Kelas I TPI Bandung Dalam Penyelenggaraan Mal Pelayanan Publik - Muhammad Darylrizqi Indrajaya; Seno Setyo Pujonggo; Rita Kusuma Astuti (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
Publik service is an activity to t fulfill the needs and expectations of public service providers towards the recipients of the service. In an effort to provide public services, especially immigration services in the city of Cimahi, the government, as the service provider, collaborates with other public service institutions. One of the forms of publicc service collaboration is presented in Cimahi is through the presence of the Cimahi Publikc Service Mall with a one-stop public service system. The services provided by the Immigration department in this context are passport services at the Cimahi Publik Service Mall, implementing the Integrated Passport Service System (SPPT). This is done to facilitate the community, especially in Cimahi, in obtaining passport services. This research is conducted to gain more information regarding to the process of the spesifc collaboration.